2005
DOI: 10.1111/j.1523-1755.2005.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the racial disparities associated with kidney disease1

Abstract: In the United States, chronic kidney disease (CKD), and in particular end-stage renal disease (ESRD), represent a growing problem. Many other countries also have an increasing number of ESRD cases. Racial/ethnic disparities have been documented globally in the prevalence, incidence, and treatment of CKD, most extensively in the United States, but also in the United Kingdom, Australia, and New Zealand, among others. In many circumstances, these disparities are of a negative nature, that is, certain racial/ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
144
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(150 citation statements)
references
References 83 publications
2
144
1
3
Order By: Relevance
“…199,200 Norris and Agodoa 201 have developed a model highlighting how socioeconomic factors such as low income, poor education, residence in low-income areas, and poor access to health care are strong predictors of the development of ESRD. Not enough study has been given to the notion that differential quality of physician care may characterize programs in different neighborhoods.…”
Section: Socioeconomic and Cultural Issuesmentioning
confidence: 99%
“…199,200 Norris and Agodoa 201 have developed a model highlighting how socioeconomic factors such as low income, poor education, residence in low-income areas, and poor access to health care are strong predictors of the development of ESRD. Not enough study has been given to the notion that differential quality of physician care may characterize programs in different neighborhoods.…”
Section: Socioeconomic and Cultural Issuesmentioning
confidence: 99%
“…In the United States, renal allograft survival is significantly lower in black than in white patients, [5][6][7][8][9][10] which might be due to higher immunologic risk, poorer medication adherence, or decreased access to pre-and posttransplantation care. 8,[11][12][13][14][15][16][17][18][19][20][21][22][23] Whether black Canadian transplant recipients also have decreased transplant survival is unclear because there are no published data describing transplant outcomes among this patient group. A recent study comparing outcomes in Canada and the United States demonstrated that American transplant recipients had an increased risk for mortality.…”
mentioning
confidence: 99%
“…Indeed, racial differences in the prevalence and risk for chronic kidney disease are striking (14), and this has been extensively studied in the black population. Clear differences in various Asian ethnic groups have also been demonstrated in Hong Kong and Singapore (15,16).…”
Section: Epidemiologic Basis For Screening For Chronic Kidney Diseasementioning
confidence: 99%